Analisa Proses Wiring Pada Produksi Panel Hubung Bagi Tegangan Rendah (PHBTR) Pasang Luar 400 Ampere – 4 Jurusan - Naufal Taufiqul Hakim; Mohammad Fatkhurrohman (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
In this modern era, of course, technology is developing rapidly and increasingly sophisticated which produces various innovations in various aspects of life, including the industrial sector, it is possible in the electrical and electrical fields. The main form of the application of technology is as a driving force for the progress of science and technology and the development of the times, in making work easier and more efficient. The research was conducted to analyze the wiring process on the low-voltage connection panel (PHB-TR) at PT. Powerindo Prima Perkasa using PLN standards. The standard used in the production of low-voltage circuit boards is the PLN standard number D3.016-2 in 2010. The research was conducted to analyze the wiring process for the low-voltage connection panels (PHB- TR) at PT. Powerindo Prima Perkasa using PLN standards. The standard used in the production of low-voltage connection panels is the PLN standard number D3.016-2 in 2010. The data collection methods in this study were conducting interviews, observations, wiring on the panels and literature studies. Based on the results of the discussion in this study, the following conclusions can be drawn: [1] Knowing what components are contained in the Low Voltage Connection Panel (PHBTR). [2] Knowing the wiring process on the Low Voltage Connection Panel (PHBTR). [3] Knowing how the Low Voltage Split Connector Panel (PHBTR).